Tarğῑḥāt Assamin Al- Halabiy in his book "Al- qawl al- wağῑz fῑ ʾaḥkām al- kitāb al- ʿazῑz" from the beginning of Surat An- nisa till verse (51) in the same Surah - Smanov, Abdulahad Abdusattar (Journal of Islamic Sciences, 2020)
The origin of this research is a scientific thesis presented by the researcher to obtain a master’s degree in Quran and Sunnah, which is titled: (Tarğῑḥāt Assamin Al- Halabiy in his book "Al- qawl al- wağῑz fῑ ʾaḥkām al- kitāb al- ʿazῑz" from the beginning of Surat An- nisa till verse (51) in the same Surat.). Assamin Al- Halabiy was among famous interpreters in his time, and his books that made him forever remembered will confirm that. He has a lot books in interpretation, and his book (Ad- durr al- maṣūn) is considered as one of important syntax interpretation’s references, and his book (Al- qawl al- wağῑz) – which I am about to discuss- is also considered as one of the largest judgment interpretations in mathab shafihiy; therefore, I concluded to study this book written by Noble Imam Assamin Al- Halabiy. In this research I compared Assamin Al- Halabiy’s speech with other famous interpreters’ speeches, and I came out with result that Assamin Al- Halabiy is mostly correct in his choices. And it cleared to me that Assamin Al- Halabiy didn’t copy from superstition’s stories, and he tried to select which is compatible with the text appears, and what genuine hadiths say; so that he can present correct reviews on syntax and poetry’s scales. However, Assamin Al- Halabiy included in his book a lot of syntax and morphology’s issues, which made his book syntax color interpretation.